Effect of the delivery route and dose of multipotent mesenchymal stem cells on the efficacy of cell therapy (review) - N. V. Pak; E. V. Murzina; N. V. Aksenova; T. G. Krylova; V. N. Aleksandrov (Вестник трансплантологии и искусственных органов)
Multipotent mesenchymal stem cells (MMSCs) are known to be excellent therapeutic agents. Apart from their ability to differentiate into various cell types, and thus participate in the repair of injured tissues and organs, they can influence the regeneration process through secretion of paracrine factors. Thus, MMSC therapy represents a special type of medical intervention that has both a systemic range of therapeutic efficacy and local activity on individual sites of an organ. Over the past decades, MMSC therapy has continuously been in a cautious transition from research development to clinically approved therapies. Clinical trial data has shown that this therapy is rarely associated with severe adverse events, is well tolerated and quite safe in the short-term period. However, it has a number of limitations for use, mainly due to the risk of malignant transformation. The success of stem cell transplantation in the treatment of various diseases has been confirmed both in preclinical studies and in clinical practice. The main issues that arise when assessing the therapeutic efficacy of MMSC-associated therapy are the type of cells (adipogenic, bone marrow, etc.), delivery route, number of cells injected, and the optimal number of injections. There is a growing body of experimental and clinical evidence suggesting that both an adequate delivery route and an adequate dose can increase the likelihood of success of MMSC-associated. Each cell delivery route has costs and benefits. However, there is generally contradictory evidence on the comparative efficacy of different cell delivery routes. The optimal dose of transplanted cells is also debated, as high MMSC doses may increase the risks of complications and may not have the proper effect both when administered systemically and locally. These aspects require further systematization of available data to maximize the effect of cell therapy by selecting the safest and most appropriate approaches.